2017
DOI: 10.1007/s00467-017-3593-8
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract obstruction: fetal intervention based on prenatal staging

Abstract: The authors present an overview of lower urinary tract obstruction (LUTO) in the fetus with a particular focus on the insult to the developing renal system. Diagnostic criteria along with the challenges in estimating long-term prognosis are reviewed. A proposed prenatal LUTO disease severity classification to guide management decisions with fetal intervention to maintain or salvage in utero and neonatal pulmonary and renal function is also discussed. Stage I LUTO (mild form) is characterized by normal amniotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 48 publications
0
50
0
1
Order By: Relevance
“…A recently published classification system with selection criteria for eligibility for fetal intervention by Ruano et al, approaches the fetus on an individual basis to provide the current best management. This classification system uses fetal renal ultrasound parameters, amniotic fluid volume, and fetal urinalysis separately . However, an individualized estimate of the postnatal renal function is not attempted.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published classification system with selection criteria for eligibility for fetal intervention by Ruano et al, approaches the fetus on an individual basis to provide the current best management. This classification system uses fetal renal ultrasound parameters, amniotic fluid volume, and fetal urinalysis separately . However, an individualized estimate of the postnatal renal function is not attempted.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a retrospective study of 72 fetuses with megacystis showed a statistically significant correlation between fetal urinary electrolytes and postnatal renal outcomes 132. The use of fetal urinary biochemistry to evaluate fetal renal function should, therefore, take into account three main considerations: (1) the available evidence is mostly based on studies that evaluated fetal urinary biochemistry during the second trimester; (2) fetal urinary biochemistry is only a “snapshot picture” of fetal renal function, which means that many other factors could influence renal function prenatally and postnatally; and (3) fetal urinary biochemistry is only a part of comprehensive fetal evaluation and should be interpreted along with fetal renal imaging for appropriate staging of disease severity 112133134135136137…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%
“…To this end, standardized prenatal LUTO diagnosis using prenatal ultrasound, fetal urine biochemistry, and clinical parameters has been proposed to improve LUTO prognostication 138139140141. A retrospective study133134138 described a prenatal LUTO staging system that correlates with postnatal survival and also proposed fetal intervention according to disease severity (table 2).…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%
See 2 more Smart Citations